Intravenous omeprazole rapidly raises intragastric pH. Issue 9 (September 1985) - Walt, R P; Reynolds, J R; Langman, M J; Smart, H L; Kitchingman, G; Somerville, K W; Hawkey, C J
Abstract : Twenty four hour intragastric acidity was measured in five duodenal ulcer patients studied at least three times. The effects of different dosage regimens of intravenous omeprazole was compared with placebo. Mean intragastric acidity from 1000 to 0800 was 34.3 +/- 4.3 mmol/l on placebo. After omeprazole 80 mg at 0900 and 40 mg at 1700 mean acidity was 2.1 +/- 0.9 mmol/l and after omeprazole 80 mg at 0900 and 80 mg at 1700 it was 0.7 +/- 0.2 mmol/l. pH remained above 4.0 for about 80% of recordings with these regimens and for only 5% with placebo. Three of the five patients also received omeprazole 80 mg at 0900, 40 mg at 1700 and 40 mg at 0100 when pH remained above 4.0 for 90% of recordings with 99% inhibition of acidity. Omeprazole rapidly raised intragastric pH in all patients and maintained a gastric pH of greater than 4.0 for most of the time. Large doses of IV omeprazole were required compared with studies using the oral compound.